2017
DOI: 10.4172/2376-0427.1000248
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Porokeratotic variant of Inflammatory Linear Verrucous Epidermal Nevus

Abstract: Inflammatory linear verrucous epidermal nevus is a rare variant of nevoid linear inflammatory dermatoses which appear most often in first six months of life and persists for many years or even whole life. Clinically it often shares many features with linear psoriasis, linear porokeratosis and other linear dermatoses which can usually be differentiated by an established set of clinical and histopathological criteria. Herein we are reporting an interesting and rare case fulfilling all the clinical and histopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Since first described by Altman and Mehregan, 2 cases of ILVEN with various histological variants have been reported. 3 Here we show that ILVEN is not a well-defined monogenic mosaic disorder but rather a heterogenous group of blaschko-linear inflammatory conditions. In our cohort, some nevi looked clinically and histopathologically as "ILVEN" but genetic analysis revealed a more precise diagnosis of CHILD nevus and linear porokeratosis.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Since first described by Altman and Mehregan, 2 cases of ILVEN with various histological variants have been reported. 3 Here we show that ILVEN is not a well-defined monogenic mosaic disorder but rather a heterogenous group of blaschko-linear inflammatory conditions. In our cohort, some nevi looked clinically and histopathologically as "ILVEN" but genetic analysis revealed a more precise diagnosis of CHILD nevus and linear porokeratosis.…”
Section: Discussionmentioning
confidence: 68%
“…Cornoid lamellae are not pathognomonic for porokeratosis and have been found in ILVEN and in 1.2% of 167 epidermal nevi in studies that did not include genetic evaluation. 3,18 Our case suggests that a fraction of individuals thought to have ILVEN may, in fact, have linear porokeratosis and emphasizes the importance of histopathologic evaluation of blaschkoid lesions. Genetic analysis revealing the biallelic PMVK mutations enabled a pathogenesis-based therapy with topical lovastatin/cholesterol, emphasizing the role of genetic evaluation in tailoring therapy for mosaic disorders.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In this study, stem cell concentration appeared to be one of the major factors affecting the degree of repigmentation. The use of NB-UVB after intraepidermal injection of melanocyte also showed highly statistically significance in repigmentation [1][2][3][4][5].As for treatment of pigmented lesion in Greece, it was found that the Alexandrite laser has excellent results for freckles, while the combination of chemical peelings and fractional laser is good for the treatment of melasma. On the other hand, a literature review was made to understand the current practice of treatment for pigmented lesions in Taiwan.…”
mentioning
confidence: 99%
“…In this study, stem cell concentration appeared to be one of the major factors affecting the degree of repigmentation. The use of NB-UVB after intraepidermal injection of melanocyte also showed highly statistically significance in repigmentation [1][2][3][4][5].…”
mentioning
confidence: 99%